Evaluation of biological activities of nine anti-inflammatory medicinal plants and characterization of antimicrobial compounds from Pomaria sandersonii and Alepidea amatymbica - Muleya, Eddwina (My University, 2013)
Medicinal plants provide valuable alternative sources of drugs and drug discovery because many have been used in traditional practices for centuries to manage or treat various forms of ailments. The aim of this study was to evaluate the biological activities of nine medicinal plants used by Zulus in Mabandla village, KwaZulu-Natal province, South Africa to treat inflammation and to isolate selected active compounds against studied pathogens from Alepidea amatymbica and Pomaria sandersonii. The plants were selected on the basis of an ethnobotanical survey based on questionnaire response and verbal interviews that were conducted in Mabandla village with the local traditional healers and herbalists. The isolation of compounds from Alepidea amatymbica and Pomaria sandersonii was based on the bioassay based study which was carried out in this study. Bioassay guided study involving in vitro anti-inflammatory measurement using soya bean derived 15 Lipoxygenase, free radical scavenging capacity against the ABTS●+ radical cation and DPPH● radicals; antimicrobial and bioautography assays against Staphylococcus aureus, ATCC 29213, Pseudomonas aeruginosa ATCC 27853, Enterococcus faecalis ATCC 29212, Escherichia coli, ATCC25922, Candida albicans, Cryptococcus neoformans and Aspergillus fumigatus were carried out using the plants extracts, fractions and pure compounds. Isolation of compounds displaying biological activity was carried out by using open column chromatography and preparative thin layer chromatography (PTLC). The compounds were characterised by use of Nuclear Magnetic resonance, (NMR) and Mass Spectrometry (MS). The DPPH sprayed TLC showed that all the nine plants contained antioxidants. Most of which were contained in polar fractions of acetone and methanol. Results of the assays displayed a range of biological activities comparable to the positive controls used for each assay. DPPH● scavenging displayed EC50 values ranging between 1.008 and 467 Kg/ml. The highest activity was observed with the methanol fraction of Berkheya setifera with an EC50 value of 1.008 Kg/ml followed by the crude extract of Gunnera perpensa with EC50 value of 1.069 Kg/ml. Carissa bispinosa hexane fraction had the lowest activity of 467.7 Kg/ml. The Pomaria sandersonii DCM extract had the highest ABTS●+ radical scavenging activity by Pomaria sandersonii DCM extract, (1.273 Kg/ml) for the ethyl acetate, (5.973 Kg/ml) while the hexane fraction from Eucomis autumnalis had the lowest activity (929.4 Kg/ml). The activity of Pomaria sandersonii extracts and fractions demonstrated that the plant contains antioxidants that react with both DPPH and ABTS radicals although higher activities were shown by ABTS as displayed by the lower EC50 values. All the crude fractions and extracts had high to moderate antibacterial activities (20-625 Kg/ml) and anti-fungal activities (20-2500 Kg /ml). Pomaria sandersonii crude and fractions had the highest antimicrobial activity compared to other plants. Some MIC values for P. sandersonii dichloromethane and ethyl acetate fractions (80 Kg/ml in each case) compared well with gentamycin (4 Kg/ml) since they showed same values against Staphylococcus aureus, Enterococcus faecalis, Escherichia coli and Pseudonomus aeruginosa. The dichloromethane, acetone and methanol fractions were also active (20 Kg/ml) against both Candida albicans and Aspergillus fumigatus. Inhibition of pathogen growth demonstrated by the polar fractions of the studied plants suggested that some of the active compounds would be soluble in water. A total of seven compounds were isolated from Alepidea amatymbica and Pomaria sandersonii. We propose three were new compounds after considering literature search involving closely related research to this investigation. These were two diterpenes from Alepidea amatymbica, namely, 14-acetoxo-12-oxokaur-16-en-19-oic acid labelled as 0657 and 16-hydroxy-kaur-6-en-19-oic acid given the label 06-2 in this study. The third suspected new compound is the chalcone dimer, which is referred to as EM86 in this study from Pomaria sandersonii. EM80-2 was obtained as a mixture of the cis and trans of 2’, 4, 4,’-trihydroxychalcone or 1-(2,4-dihydroxyphenyl)-3-(4-hydroxyphenyl)-2-propen-1-one, from Pomaria sandersonii. The three diterpenes, 14-acetoxokaur-16-en-19-oic acid (0652), 13-hydroxy-16-kauren-19-oic acid (06B) and 14-oxokaur-16-en-19-oic acid (06431) were isolated from Alepidea amatymbica for the first time. Isolated compounds were further tested as individual compounds and results showed that 16-hydroxy-kaur-6-en-19-oic acid (06-2) had weak activity against tested bacteria and fungi with the MIC: Staphylococcus aureus (320 Kg/ml) and Candida albicans, (320 Kg/ml). On the other hand 13-hydroxy-kaur-16-en-19-oic acid (06B) was more active against, Staphylococcus aureus (160 Kg/ml) and Aspergillus fumigatus (40 Kg/ml). The yellow compound that was isolated from Pomaria sandersonii, 1-(2, 4-ihydroxyphenyl)-3-(4-hydroxyphenyl)-2-propen-1-one was antimicrobial with the following MICs: Candida albicans: 80 Kg/ml; Pseudomonas aeruginosa, Escherichia coli, Enterococcus faecalis, Staphylococcus aureus: 160 Kg/ml and Aspergillus fumigatus: 625 Kg/ml. There were two mixtures referred to as EM 49 and EM 77 from Pomaria sandersonii which were difficult to purify but had anti-microbial inhibitory activities worth reporting. EM49 had MIC against Candida albicans of: 160μg/ml; Pseudomonas aeruginosa: 320 Kg/ml, Escherichia coli: 80μg/ml, Enterococcus faecalis 80μg/ml, and Staphylococcus aureus: 80μg/ml and Aspergillus fumigatus: 320μg/ml. EM 77 had MIC against Escherichia coli: 80 Kg/ml and Cryptococcus neoformans: 80μg/ml. Further work on their purification need to be done since in this research we are just reporting on their high MIC activities. The medicinal plants used to treat inflammation under different disease conditions in the Zulu community of Mabandla village, Kwa-Zulu Natal, South Africa have some relevant biological activities. The various antimicrobial, antioxidant and anti-inflammatory activities support the validity of their healing capacities that the traditional healers of the community claim to possess. Although there is evidence of good antimicrobial, antioxidant and anti-inflammatory activities by the crude extracts, the high levels of sucrose in P. prunelloides and glucose in G. perpensa should be borne in mind when using their decoctions in traditional medicine particularly by diabetic patients. In vitro results for the antioxidant, antinflammtory and antimicrobial activities carried out in this investigation illustrate that the plants can be a source of treatment and management for inflammation related conditions. These therefore justify their use in Zulu traditional medicine. However, in vivo assays should be carried out in order to completely validate claims by the traditional healers that they treat inflammation related conditions.
D. Tech. (Department of Chemistry, Faculty of Applied and Computer Sciences)|, Vaal University of Technology.
Keywords: Medicinal plants.; Inflammation treatment; Alepidea amatymbica; Pomaria sandersonii; Ethno-botanical survey; Traditional healers; Mabandla village; Zulu traditional medicine; Berkheya setifera; Gunnera perpensa; Carissa bispinosa; Eucomis autumnalis; 660.6; Medicinal plants -- Biotechnology; Plant biotechnology; Anti-inflammatory agents.